2014
DOI: 10.1371/journal.pone.0089206
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Perioperative Venous Thromboembolism in Japanese Gynecological Patients

Abstract: ObjectiveTo develop a convenient screening method that can predict perioperative venous thromboembolism (VTE) and identify patients at risk of fatal perioperative pulmonary embolism (PE).MethodsPatients hospitalized for gynecological abdominal surgery (n = 183) underwent hematology tests and multidetector computed tomography (MDCT) to detect VTE. All statistical analyses were carried out using the SPSS software program (PASWV19.0J)ResultsThe following risk factors for VTE were identified by univariate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…The symptomatic postoperative DVT incidence was consistent with the previous study. 17 We found that the DVT incidence is much higher than previous reports in patients with gynecological malignant tumor. 6 , 18 Aside from different design of study, the patient population contributes to the discrepancy.…”
Section: Discussioncontrasting
confidence: 54%
“…The symptomatic postoperative DVT incidence was consistent with the previous study. 17 We found that the DVT incidence is much higher than previous reports in patients with gynecological malignant tumor. 6 , 18 Aside from different design of study, the patient population contributes to the discrepancy.…”
Section: Discussioncontrasting
confidence: 54%
“… 13 16 Plasmin-α2-plasmin inhibitor complex, an irreversible complex of plasmin and a2-plasmin inhibitor, is considered as a satisfactory indicator of an enhanced fibrinolytic state in vivo because it is almost undetectable in normal persons and expected to be more useful for the clinical assessment of VTE in patients with a high-risk perioperative VTE. 17 , 18 Besides, t-PAIC, the 1:1 covalent inactive complex of tPA and PAI-1, has been proposed as a marker of the fibrinolytic system in the diagnosis of acute myocardial infarction (MI), stroke, and VTE. 19 21 Moreover, regarded as a marker of endothelial lesion, sTM, the glycoprotein appears in human urine and plasma in a truncated form of TM without transmembrane and cytoplasmic domains, is involved in this panel as well.…”
Section: Introductionmentioning
confidence: 99%
“…Lower PAP levels are associated with subsequent coronary events in patients with a history of MI . A previous study demonstrated that PAP is useful for predicting the risk of perioperative VTE and for identifying patients with a high risk of fatal perioperative PE . tPAI‐C is a complex of t‐PA with its type 1 inhibitor (PAI‐1) which has been reported to be of practical value in assessing risk of MI and VTE for both genders, especially for smokers or diabetes mellitus patients .…”
Section: Introductionmentioning
confidence: 99%
“…11 A previous study demonstrated that PAP is useful for predicting the risk of perioperative VTE and for identifying patients with a high risk of fatal perioperative PE. 12 tPAI-C is a complex of t-PA with its type 1 inhibitor (PAI-1) which has been reported to be of practical value in assessing risk of MI and VTE for both genders, especially for smokers or diabetes mellitus patients. 13,14 PAI-1 is synthesized from the endothelial cells as an active molecule, but it then spontaneously converts to a latent form, which can be partially reactivated in vitro.…”
Section: Introductionmentioning
confidence: 99%